(untitled) (REMUNOM, 2025)
The study in hand aims to explore the factors surrounding the divorced marital status, in order to promote a legal analysis about the relevance of maintaining the use of this marital status, in the context of the 21st century. Throughout the study the multidisciplinary aspect of the matter becomes clear, in a way that was brought into discussion legal, historical and social aspects arising from the use of this classification. The research was developed based on bibliographical review of legal doctrine and academical studies, analysis of current and repealed laws, as well as the study of Bill no 5.083/2020. The study seeks to contribute to the discussion about the existence or not of the relevance of maintaining the divorced marital status in Brazilian legal system.